Estimasi Timbulan Sampah dan Luas Lahan Tempat Pemrosesan Akhir Sampah (TPA) di Kota Kupang - Oktavina G. LP Manulangga (INSOLOGI: Jurnal Sains dan Teknologi, 2022)
The city of Kupang is one of the developing cities and this has an effect on people's lifestyles and consumption patterns. The increasing purchasing power and competitiveness of the community towards various types of basic materials and technological products make a major contribution so that it indirectly contributes to the quality and quantity of waste. The final waste processing site (TPA) in Kupang City is located in Alak District with an area of ​​9.14 Ha and has been operating since 1998. Based on DLHK calculation data, the amount of waste generated every day is 86 tons of waste. The operation of the Alak TPA uses the controlled landfill method, but in practice the waste that enters the TPA does not go through a sorting and recycling process, but is directly disposed of in a landfill which is then covered with white soil and pressed with heavy equipment. The generation of waste in Kupang City has increased every year because not all waste can be managed properly. The problem of waste management in Kupang City is the limited capacity at the TPA, the slow processing of waste, and the increasing volume of waste, so that it is necessary to carry out a systematic, comprehensive and sustainable waste management including limiting waste generation, recycling waste, and/or reuse. rubbish. Determination of the location of the urban waste landfill must pay attention to the city development plan, the economic capacity of the local government as well as the physical and geological conditions of the planned area and must be in accordance with the planned period so that there is no accumulation of waste that can have an impact on health, environment and social and economics due to lack of land availability for waste disposal. Therefore, it is necessary to estimate the amount of waste generated in the City of Kupang and determine the need for land area to accommodate waste in landfills according to the plan period. Based on the results of the study, the total amount of waste generated in the planning year period was 8,336,498.4 m3 with a landfill area of ​​63.92 Ha, and a buffer area of ​​15.98 Ha. The soil covering the waste layer to be compacted in the TPA on the surface of the waste is about 15 m from the thickness of the pile.